On the Track of the Missing tRNA Genes: A Source of Non-Canonical Functions? - Ehrlich, Ricardo; Davyt, Marcos; López, Ignacio; Chalar, Cora; Marín, Mónica (Frontiers in Molecular Biosciences, 2021)
Cellular tRNAs appear today as a diverse population of informative macromolecules with conserved general elements ensuring essential common functions and different and distinctive features securing specific interactions and activities. Their differential expression and the variety of post-transcriptional modifications they are subject to, lead to the existence of complex repertoires of tRNA populations adjusted to defined cellular states. Despite the tRNA-coding genes redundancy in prokaryote and eukaryote genomes, it is surprising to note the absence of genes coding specific translational-active isoacceptors throughout the phylogeny. Through the analysis of different releases of tRNA databases, this review aims to provide a general summary about those “missing tRNA genes”. This absence refers to both tRNAs that are not encoded in the genome, as well as others that show critical sequence variations that would prevent their activity as canonical translation adaptor molecules. Notably, while a group of genes are universally missing, others are absent in particular kingdoms. Functional information available allows to hypothesize that the exclusion of isodecoding molecules would be linked to: 1) reduce ambiguities of signals that define the specificity of the interactions in which the tRNAs are involved; 2) ensure the adaptation of the translational apparatus to the cellular state; 3) divert particular tRNA variants from ribosomal protein synthesis to other cellular functions. This leads to consider the “missing tRNA genes” as a source of putative non-canonical tRNA functions and to broaden the concept of adapter molecules in ribosomal-dependent protein synthesis.